2012
DOI: 10.1007/s11701-012-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted whipple’s operation for solid pseudopapillary tumour of pancreas

Abstract: Solid pseudopapillary tumor is a rare tumor of the pancreas. They are slow growing with low malignant potential. The prognosis is excellent after surgical resection. Here we report a case of solid pseudopapillary tumor of the pancreas at the uncinate process. There are increasing interests about minimal access surgery for pancreatic lesion. However conventional laparoscopic Whipple's operation is technically difficult. With the benign characteristic of this tumor, as well as the advance in robotic surgery, rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In recent years, as laparoscopic and robotic technology has been developing, due to minimally invasive advantages, it was expected to become one of the ways of SPTP treatment because tumors were generally benign and represented thick fibrous capsule. The clinical outcome of laparoscopic and robotic excision of pancreatic tumors in the Chinese high-volume medical center was satisfactory [24,33,34]. Furthermore, the robotic technique seemed to be more efficient and secure than a laparoscope among properly selected patients [35].…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, as laparoscopic and robotic technology has been developing, due to minimally invasive advantages, it was expected to become one of the ways of SPTP treatment because tumors were generally benign and represented thick fibrous capsule. The clinical outcome of laparoscopic and robotic excision of pancreatic tumors in the Chinese high-volume medical center was satisfactory [24,33,34]. Furthermore, the robotic technique seemed to be more efficient and secure than a laparoscope among properly selected patients [35].…”
Section: Discussionmentioning
confidence: 98%
“…The most popular techniques include end-to-side duct-to-mucosa anastomosis and end-to-end dunking or invagination anastomosis ( 20 , 21 ); other methods were mostly modified from the above techniques ( 22 24 ). End-to-side duct-to-mucosa anastomosis is one of the most popular techniques, as it is thought as the most histologically compatible and has been reported to have excellent results in adults ( 5 , 22 , 25 ). Spagnoletti et al performed PPPD and reported a successful end-to-side duct-to-mucosa anastomosis in a 5-month-old patient; the authors determined the method to be safe for pediatric patients ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…PD is widely accepted as one of the most complicated procedures in general surgery because of the wide dissection and three anastomoses involved. Robotic PD in adults has been reported to have better efficacy and safety (3,25,33,34). Despite the reported advantages of robotic surgery, this approach is rarely used in pediatric surgery with only a few published reports (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient underwent R-PPPD and we followed ERAS protocol in postoperative period and she was discharged on POD6. On reviewing literature, we found very few evidences of doing R-PPPD in young females for SPT,[ 9 10 ] and according to our literature search, she is the youngest patient who underwent R-PPPD for SPT. We believe R-PPPD can be done in paediatric and adolescent age group with ease and faster postoperative recovery with equivalent oncological outcome.…”
Section: Discussionmentioning
confidence: 99%